2008
DOI: 10.1128/jb.00742-08
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 4-Nitrophenol Oxidation in Rhodococcus sp. Strain PN1: Characterization of the Two-Component 4-Nitrophenol Hydroxylase and Regulation of Its Expression

Abstract: 4-Nitrophenol (4-NP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 47 publications
2
51
0
Order By: Relevance
“…5 and Table 2) also contributes to the general understanding of reactions of its homologs identified by SSN analysis (supplemental Fig. S1) (9,10,13,(33)(34)(35). These enzymes were identified in microbes that showed potential in bioremediation applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and Table 2) also contributes to the general understanding of reactions of its homologs identified by SSN analysis (supplemental Fig. S1) (9,10,13,(33)(34)(35). These enzymes were identified in microbes that showed potential in bioremediation applications.…”
Section: Discussionmentioning
confidence: 99%
“…S1) showed that there are 2,839 enzymes in which the sequences have Ͼ34% identity with HadA, and only 11 of these 2,839 enzymes were reviewed by UniProt. The enzymes identified to be homologous to HadA were mostly flavin-dependent monooxygenases that incorporate a hydroxyl group into phenols such as CPs or nitrophenols (9,10,(33)(34)(35). As these enzymes showed potential applications in bioremediation of toxic compounds, the understanding of kinetic mechanisms associated with a flavin-dependent dechlorinase (HadA) reported herein should also be useful for giving an overall picture about the reaction mechanism of these enzymes in general.…”
mentioning
confidence: 99%
“…(182), Rhodococcus opacus SAO101 (100), and Rhodococcus sp. PN1 (192) all use a monooxygenase that directly oxidizes 4-nitrophenol to benzoquinone, followed by reduction to hydroquinone (182). The pathways converge at ring cleavage, where 1,2,4-trihydroxybenzene and hydroquinone are each converted into maleylacetate, which is then reduced to ␤-ketoadipate and converted to TCA cycle intermediates.…”
Section: Pathways For Nitrophenol Catabolismmentioning
confidence: 99%
“…More recently, a twocomponent PNP hydroxylase from Rhodococcus sp. strain PN1 that catalyzes the hydroxylation of PNP to form 4-nitrocatechol was characterized (32). Although the PNP catabolic genes for the hydroquinone pathway were reported to have been cloned from Pseudomonas sp.…”
mentioning
confidence: 99%